Notes for thinking about a liberating intercultural university of our America - BONILLA , Alcira (Utopía y Praxis Latinoamericana, 2022)
We start from the thesis that Raúl Fornet-Betancourt's university program results from the conjunction of his intercultural philosophical positioning with the investigation of the historical forms, particularly in Latinamerica, in which philosophical teaching has manifested itself. Secondly, the alternative university proposals of the Brazilian philosopher Marilena Chauí and those of Boaventura de Sousa Santos, a Portuguese sociologist widely spread in the Southern Cone, are analyzed. In subsequent dialogue with these positions, the innovative force of the intercultural "conjura" to which the honored philosopher appeals and its relevance for Nuestra América (“Our America”) becomes evident.